The Effect of DPR, SIZE, ROA, and DER on PBV Empirical Study on Food and Beverage Sector Companies Listed on the IDX for the 2018-2021 Period - Lisiantara, Gregorius Anggana (Universitas Syiah Kuala, 2025)
The Food adn Beverages industry is expanding, but the presence of the COVID-19, which began in 2019, has prompted the company to make changes to internal and external rules that have an influence on firm value. As a result, the purpose of this study was to examine the impact of dividend payout ratio, size, return on asset, and debt to equity on firm value in Food and Baverages industry companies listed on the Indonesian Stock Exchange from 2018 to 2021. This study has a total of 55 were collected. For data verification, use multiple regression analysis. According to the study's findings, dividend payout ratio and size have no effect on firm value, however return on asset and debt to equity ratio have positive significant effect on firm value.